Relationships between measurements of fat deterioration during heating and frying in RBD olein - Augustin, M.A.; Asap, Telingai; Heng, L.K. (Springer-Verlag, 1987)
The relationships between measurements of fat deterioration during static heating and heating with intermittent frying of potato crisps in RBD olein in the presence and absence of TBHQ were evaluated. Significant linear relationships were found between iodine value, C18:2/C16:0 ratio, polar components and dielectric constant. Nonlinear relationships were found between smoke point, acid value and polar components. The relationships between polymer content and polar components, E 1 cm 1% at 232 nm and wavelength (λ) for which E 1 cm 10% =1 also were found to be nonlinear.